1985
DOI: 10.1002/fut.3990050110
|View full text |Cite
|
Sign up to set email alerts
|

The economics of performance margins in futures markets

Abstract: erhaps no other subject area in the futures industry is as misunderstood as P the function of margins. Margins in futures markets perform different economic functions from margins in securities markets. However, people often mistakenly assume the functions are the same because the same terms are used. A margin in the securities market is a down payment for the security and results in an extension of credit. A margin in the futures market is essentially earnest money and represents a good-faith deposit to guara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Traditionally, futures exchanges use margins as a risk management tool; they are a payment that serves as a collateral deposit to eliminate credit risk (e.g., Telser 1981, Figlewski, 1984, Kahl et al, 1985, Gay et al, 1986, Fenn and Kupiec, 1993, Gemmill, 1994. Till recently, futures exchanges had the discretion to set and change margin rules.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, futures exchanges use margins as a risk management tool; they are a payment that serves as a collateral deposit to eliminate credit risk (e.g., Telser 1981, Figlewski, 1984, Kahl et al, 1985, Gay et al, 1986, Fenn and Kupiec, 1993, Gemmill, 1994. Till recently, futures exchanges had the discretion to set and change margin rules.…”
Section: Introductionmentioning
confidence: 99%
“…Indccd, many earlier academic studies have concluded that historically, margin requirements in futures markets have performed well in preventing contractual defaults and may be, on average, conservatively high. [See Telser (1 98 1); Figlewski (1984); Edwards and Neftci ( 1985); Kahl, Rutz, and Sinquefield (1985); Brennan (1986); Gay, Hunter, and Kolb (1 986); Estrella (1988);and Craine (1992)l. Some also argue that any attempt to force a drastic increase in margin requirements in stock index futures contracts would drive trading volume overseas and hurt the liquidity and viability of U.S. futures markets [Miller (1990)].…”
Section: Introductionmentioning
confidence: 99%
“…Markham (1987) shows that margin requirements have been an integral part of the modern futures trading from the very beginning. For the purpose of margin, also seeTelser (1981), andKahl, Rutz, and Sinquefeld (1985).…”
mentioning
confidence: 99%